INTEGRATIVE MANAGEMENT OF CHRONIC KIDNEY DISEASE: A CASE REPORT ON THE EFFICACY OF AYURVEDIC PANCHAKARMA THERAPY IN ADVANCED CKD (Prakriti - The International Multidisciplinary Research Journal, 2024)
Chronic kidney disease (CKD) constitutes a significant global health challenge,  ranking among the foremost causes of morbidity and mortality. The effective  management of CKD by primary care providers is imperative to mitigate the risk  of complications, including cardiovascular disease, progression to end-stage renal  disease (ESRD), and premature mortality. The integration of traditional approaches,  such as Ayurveda, with conventional management strategies offers a comprehensive  framework for CKD management. A 73-year-old male with a documented history of hypertension and a recent diagnosis  of CKD Stage V presented to Jeena Sikho Lifecare Limited Hospital exhibiting  symptoms such as pedal edema, periorbital swelling, and gastric disturbances.  The patient underwent Panchakarma therapy, Ayurvedic medication, and lifestyle  and dietary modifications. Substantial symptom relief was observed following the  integrative treatment approach.
Keywords: Chronic Kidney Disease (CKD); Panchakarma in Ayurveda; Hypertension; End-Stage Renal Disease (ESRD); Integrative Medicine; Vrikka Vikar